Microbial Communities of the Drinking Water With Gradient Radon Concentration Are Primarily Contributed by Radon and Heavy Metal Content - Nayak, Tilak; De, Debjit; Karmakar, Parimal; Deb, Argha; Dhal, Paltu Kumar (Frontiers in Environmental Science, 2021)
Radon and heavy metal (HM) contamination in drinking water and their impact on health have been reported earlier. However, yet, relatively little is known about the microbial community in the drinking water with gradients of radon and the drivers of microbial community patterns in such water. With this view, we first examine microbial dynamics of drinking water in the permissible level 93±2 Bq/l (control), 510±1.5 6 Bq/l and 576±2 Bq/l as medium and 728±3 Bq/l as high radon containing tube wells from Dumka and Godda district, which comes under a major fault of eastern fringes, India. Attempts have also been made to predict the impact of radon contamination gradient and other water environmental parameters on community structure. The measured physicochemical character revealed strong clustering by sampling site with respect to their radon and HM content. The radon contaminated sites represent HM rich nutrient-limited sites compared to control. The Radon (Rn), HM (Pb, Cu and As) and total suspended solids (TSS) were the most determinant variable among the parameters and influenced the microbial community composition of that region. The microbial diversity of those sites was less diverse and this measured diversity decreased gradually on the sites with an increased gradient of radon contamination. The dominant microbial family in contaminated sites were Moraxellaceae, Chitinophagaceae, unclassified Candidatus Azambacteria, unclassified Candidatus Moranbacteria, unclassified Candidatus Collierbacteria and Gammaproteobacterial members which are reported to be abundantly inhabitant in radiation and chemolithotrophic environments pose better radionuclides protective mechanisms while the bacterial members dominant in control site Comamonadaceae, Rhodocyclaceae, Nitrospirales Incertae Sedis, cvE6, unclassified Woesearchaeota (DHVEG-6), and Holophagaceae reported to adundant in natural soil and drinking water labile to harsh environments. Relative sequence abundance of Comamonadaceae was decreasing on the sites with increasing radon gradient while the opposite trend observed for Chitinophagaceae. The distribution of such microbial assembles is linked to radon and heavy metal, highlighting that taxa with distinct environmental preferences underlie apparent clustering by sites, thus can utilize them for biostimulation based in-situ bioremediation purpose.